1987
DOI: 10.1111/j.1476-5381.1987.tb11322.x
|View full text |Cite
|
Sign up to set email alerts
|

External ATP mimics carbachol in initiating calcium mobilization from pancreatic β‐cells conditioned by previous exposure to glucose

Abstract: 1 Exposure to ATP (2-200 pM) resulted in a prominent peak of 45Ca efflux, when P-cell-rich pancreatic islets from ob/ob-mice were perifused with a Ca2+-deficient medium. ADP and the stable /x/p-methylene analogues of ATP and ADP also had stimulatory effects. 2 The nucleotide initiation of "5Ca efflux mimicked that obtained with carbachol both in requiring previous exposure to glucose and in being more pronounced after replacing extracellular Na+ by K+. 3 It was possible to induce repeated peaks of stimulated 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…It can be observed that this substitution shifts the reversal potential to more positive potentials from a value of -5-5 mV in 100 % to + 1-2 mV in 50 % Cl-. The magnitude of this shift is close to the value of the shift of the equilibrium potential of Cl-ions by a 50 % reduction of (Benham, 1989b (Hallam & Pearson, 1986;Gylfe & Helman, 1987;McMillian, Soltoff, Cantley & Talamo, 1987;Phaneuf et al 1987;Tawada et al 1987;Fine, Cole & Davidson, 1989; Pearce, Murphy, Jeremy, Morrow & Dandona, 1989;Sasakawa, Nakaki, Yamamoto & Kato, 1989). It and in rabbit portal vein (Byrne & Large, 1988).…”
Section: Atp Releases Ca2+ From Intracellular Storessupporting
confidence: 64%
“…It can be observed that this substitution shifts the reversal potential to more positive potentials from a value of -5-5 mV in 100 % to + 1-2 mV in 50 % Cl-. The magnitude of this shift is close to the value of the shift of the equilibrium potential of Cl-ions by a 50 % reduction of (Benham, 1989b (Hallam & Pearson, 1986;Gylfe & Helman, 1987;McMillian, Soltoff, Cantley & Talamo, 1987;Phaneuf et al 1987;Tawada et al 1987;Fine, Cole & Davidson, 1989; Pearce, Murphy, Jeremy, Morrow & Dandona, 1989;Sasakawa, Nakaki, Yamamoto & Kato, 1989). It and in rabbit portal vein (Byrne & Large, 1988).…”
Section: Atp Releases Ca2+ From Intracellular Storessupporting
confidence: 64%
“…In the dog mesenteric artery, nifedipine can selectively inhibit the purinergic component of the contractions evoked by sympathetic nerve stimulation (Omote et al, 1989), and in snail neurones nanomolar concentrations of extracellular ATP can activate membrane calcium channels (Yatani et al, 1982). Also, P2-purinoceptor-mediated calcium mobilization across the cell membrane has been observed in rat isolated alveolar type II cells (Dorn et al, 1989), murine thymocytes (El-Moatassim et al, 1989), human promyelocyteic cell line HL60 (Nonotte et al, 1989), Ehrlich ascites tumour cells (Dubyak & De Young, 1985), pancreatic i-cells (Gylfe & Hellman, 1987) and rat parotid acinar cells (McMillian et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…PLC activity was early detected in rodent islets (Schrey and Montague, 1983;Dunlop and Larkins, 1986), and subsequent analyses have demonstrated islet expression of several PLC-β, -γ, and -δ isozymes Zawalich et al, 1995;Gasa et al, 1999;Zawalich and Zawalich, 2000;Kim et al, 2001a;Kim et al, 2001b). The importance of PLC activity for insulin secretion is underlined by the fact that the enzyme is activated not only after exposure of islets and β-cells to various G-protein coupled receptor stimuli, such as acetylcholine/carbachol (Best and Malaisse, 1983;Hellman and Gylfe, 1986a;Best et al, 1987;Biden et al, 1987;Gilon and Henquin, 2001) and ATP (Gylfe and Hellman, 1987;Blachier and Malaisse, 1988), but also after exposure to glucose (Axen et al, 1983;Best and Malaisse, 1983;Laychock, 1983;Montague et al, 1985) and depolarizing agents (Laychock, 1983;Mathias et al, 1985;Best et al, 1987;Biden et al, 1987;Zawalich and Zawalich, 1988 (Prentki et al, 1988;Gylfe, 1991;Hellman et al, 1992;Theler et al, 1992;Miura et al, 1996) and these oscillations are characterized by a much shorter period than the glucose-induced, slow oscillations described above. Most of the [Ca 2+ ] i -elevating effect is due to IP 3 -mediated Ca 2+ mobilization from the ER, but the emptying of the stores also triggers Ca 2+ entry through store-operated channels in the plasma membrane (Liu and Gylfe, 1997;Miura et al, 1997;Dyachok and Gylfe, 2001).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 99%